M-COMMERCE: A LITERATURE REVIEW FOCUSED ON THE SERVICE OFFERORS - Schneider, Wilnei Aldir; Tezza, Rafael (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
This research aimed at the identification of advantages and challenges that organizations face when offering m-commerce service. We conducted a systematic search in the literature and a bibliometric study. The sixteen articles found were classified and analyzed descriptively by content analysis, so that the reported results could be presented and discussed. Regarding the results of this research, the following ones may be listed: there are few studies that analyze the providers of m-commerce service; there is no specific journal that publishes studies with this specific focus; the existing researches are not focused on a specific business sector; there are several benefits that a company may obtain by offering m-commerce, however, there are also barriers that need to be overcome; and some guidelines might be followed for the success of the m-commerce market.